2023
DOI: 10.3390/antibiotics12030525
|View full text |Cite
|
Sign up to set email alerts
|

Estimation, Evaluation and Characterization of Carbapenem Resistance Burden from a Tertiary Care Hospital, Pakistan

Abstract: Carbapenem resistance has become major concern in healthcare settings globally; therefore, its monitoring is crucial for intervention efforts to halt resistance spread. During May 2019–April 2022, 2170 clinical strains were characterized for antimicrobial susceptibility, resistance genes, replicon and sequence types. Overall, 42.1% isolates were carbapenem-resistant, and significantly associated with Klebsiella pneumoniae (K. pneumoniae) (p = 0.008) and Proteus species (p = 0.043). Carbapenemases were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…β-lactam resistance genes appeared in a higher percentage of isolates than in many previous studies, specially bla NDM and bla CTX-M1 [ 43 , 44 ]. The bla CTX m group of genes among the multidrug-resistant E. coli were previously found to be associated with extraintestinal infections in Bangladesh [ 44 ].…”
Section: Discussionmentioning
confidence: 70%
“…β-lactam resistance genes appeared in a higher percentage of isolates than in many previous studies, specially bla NDM and bla CTX-M1 [ 43 , 44 ]. The bla CTX m group of genes among the multidrug-resistant E. coli were previously found to be associated with extraintestinal infections in Bangladesh [ 44 ].…”
Section: Discussionmentioning
confidence: 70%
“…Our analysis demonstrated 80.7% carbapenemase producer CRPA isolates, which is higher as compared to global reports such as 25.07% and 33% from 17 health facilities in 12 countries [90,91]. However, variable rates are reported in Pakistan: 18.4% and 52% [21,92]. The variability observed among carbapenemase-producing CRPA prevalence might be due to the deficient testing efforts for detecting P. aeruginosa carbapenemase production suggesting a possible higher prevalence than reported [91].…”
Section: Discussionmentioning
confidence: 48%
“…We collected 249 CRPA clinical isolates from March 2022 to April 2023 to analyze carbapenem-resistant mechanisms. Previously, variable rates of CRPA prevalence were observed in Pakistan, such as 81.6% in 2019 [69], 60% in 2014 [70], 57% in 2020 [71], 44% in 2022 [21] and 5.12% in 2023 [72]. This variability might be attributed to lower sample size in such studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These studies reported bla NDM to be the most prevalent genetic determinant for carbapenem resistance. Gondal et al, reported high levels of carbapenem resistance in K. pneumoniae 46.3% (309/668) and E. coli 41% (223/544) from tertiary care hospital [ 119 ].…”
Section: Resultsmentioning
confidence: 99%